Adherence to evidence‐based pressure injury prevention guidelines in routine clinical practice: a longitudinal study. Issue 6 (25th July 2017) - Chaboyer, Wendy; Bucknall, Tracey; Gillespie, Brigid; Thalib, Lukman; McInnes, Elizabeth; Considine, Julie; Murray, Edel; Duffy, Paula; Tuck, Michelle; Harbeck, Emma
Abstract: The aim of this longitudinal study was to describe adherence to evidence‐based pressure injury (PI) prevention guidelines in routine clinical practice in Australian hospitals. Data were analysed from four control sites of a larger‐cluster randomised trial of a PI intervention. The sample of 799 included 220 (27·5%) Not at risk, 344 (43·1%) At risk and 110 (13·8%) At high risk patients. A total of 84 (10·5%) patients developed a PI during the study: 20 (9·0% of 220) in the Not at risk group, 45 (13·1% of 344) in the At risk group, 15 (13·6% of 110) in the At high risk group and 4 (3·2% of 125) patients who did not have a risk assessment completed. Of all patients, 165 (20·7%) received only one PI prevention strategy, and 494 (61·8%) received ≥2 strategies at some point during the study period. There was no statistical difference in the proportion of time the three risk groups received ≥1 and ≥2 strategies; on average, this was less than half the time they were in the study. Thus, patients were not receiving PI prevention strategies consistently throughout their hospital stay, although it is possible patients' risk changed over the study period.